Terahertz-Sensitive Diagnosis of Charge Carriers for Thermoelectrics - Ziran Zhao (Research)
This commentary highlights the importance and implications of the study “Quadruple-band synglisis enables high thermoelectric efficiency in earth-abundant tin sulfide crystals”, led by C. Chang and L. Zhao, published in Science. They improved the thermoelectric efficiency by activating quadruple-band synglisis and facilitating carrier transport in tin sulfide crystals, and successfully developed an optical pump–terahertz probe technique in reflection mode to diagnose the carrier dynamics for high-conductivity bulk thermoelectric materials. This study inspires mutual promotion and complementary development between the fields of thermoelectrics and terahertz technology.